Expression of aerobactin genes by Shigella flexneri during extracellular and intracellular growth. - Headley, V (1997)
The expression of the Shigella flexneri chromosomal aerobactin genes during growth of the bacterium within tissue culture cells was assayed. During intracellular growth, aerobactin promoter activity was repressed relative to the level observed in bacteria grown extracellularly, even when the bacteria had been starved for iron prior to infection. Similarly, the level of one of the proteins encoded by this operon, the aerobactin outer membrane receptor, Iut, was reduced in the intracellular environment. These studies indicate that the aerobactin system is not highly expressed by bacteria within host cells, suggesting that siderophore-independent iron acquisition systems can provide essential iron during intracellular multiplication.